An evaluation of electronic services offered to Master's students by the University of the Western Cape academic library as an effort to bridge the digital divide - Nyahodza, Lena (Library and Information Studies Centre (LISC), 2016)
Academic libraries are challenged to meet the demands of patrons as expectations shift towards remote access to library services. In Africa, such challenges are exacerbated by the legacy of the digital divide. In this post-apartheid period South Africa has acknowledged the presence of a multifaceted digital divide, and that the inequalities established in the past have not yet been resolved. Therefore, academic libraries could be of great value in playing emancipatory roles through the provision of technologies and other resources that enable access to information by marginalised communities. The aim of the study is to evaluate the electronic services provided by UWC academic library to Master's Students and determine if efforts made to bridge the digital divide are perceived by users as effective, through investigating use of internet-connected infrastructure, skills development programmes established to promote adequate use of the e-services, and identification of challenges experienced by users as they interact with e-services. The study employed a qualitative research method, grounded in phenomenological design and supported by Critical Theory. Data was collected from two samples drawn using purposive sampling from the target population of Master's students and librarians. Data collection from students was facilitated through an online survey and six librarians were interviewed. Main themes that guided the dialogue during data collection emanated from reviewed literature. The study concludes that UWC library has emerged as a competent agent of democracy, having implemented several projects to support marginalised academic students in accessing information. The library has provided ICTs, bandwidth and skills development programmes to support students. However, the challenges encountered are diverse, and income imbalances among communities still prevail, indicating that projects and programmes established by university libraries to bridge the divide need to be ongoing and sustainable since the phenomenon cannot be exterminated.